2009
DOI: 10.1007/s11232-009-0079-2
|View full text |Cite
|
Sign up to set email alerts
|

Exact solutions of a generalized Boussinesq equation

Abstract: We analyze a generalized Boussinesq equation using the theory of symmetry reductions of partial differential equations. The Lie symmetry group analysis of this equation shows that the equation has only a two-parameter point symmetry group corresponding to traveling-wave solutions. To obtain exact solutions, we use two procedures: a direct method and the G /G-expansion method. We express the traveling-wave solutions in terms of hyperbolic, trigonometric, and rational functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 17 publications
(15 reference statements)
0
7
0
Order By: Relevance
“…Remarkably, it has been shown that the Boussinesq equation admits the solitary wave solution [37,38]…”
Section: Continuum Modelmentioning
confidence: 99%
“…Remarkably, it has been shown that the Boussinesq equation admits the solitary wave solution [37,38]…”
Section: Continuum Modelmentioning
confidence: 99%
“…where h(z) = sn(z, ) is a solution of (21), and taking into account that sn(z, ) = tanh(z), we obtain that for µ = and ω =…”
Section: Travelling Wave Solutionsmentioning
confidence: 99%
“…A great progress has being made in the development of methods and their applications for nding solitary traveling-wave solutions of nonlinear evolution equations. Many solutions of nonlinear partial di erential equations have been found by one or other of these methods [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Wazwaz [5] employed a combination of Hirota's method and Hereman's method to formally study (3) and derived two soliton solutions of (3). Some other work concerning symmetries and exact solutions of some Boussinesq equations can be seen in [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%